Association of MPO levels with cardiometabolic disease stratified by atherosclerotic cardiovascular risk and intensity of therapy in a workforce population - Olga A. Iakoubova; Farnoosh Haji-Sheikhi; Judy Z. Louie; Charles M. Rowland; Andre R. Arellano; Lance A. Bare; Charles E. Birse; Marc S. Penn (Scientific Reports)
Abstract Cardiometabolic risk increases cardiovascular (CVD), chronic kidney (CKD) and non-alcoholic fatty liver (NAFLD) disease risk. High myeloperoxidase (MPO) levels identify individuals at risk for CVD. We whether elevation of MPO associated with kidney and liver disease risk in subgroups stratified by ASCVD risk and intensity of therapy. Adjusted logistic models assessed the associations of MPO with markers of kidney disease (estimated glomerular filtration rate) and liver fibrosis (NAFLD score > 0.676 or Fibrosis-4 [FIB-4] score > 2.67) across ASCVD risk (low < 7.5%; intermediate 7.5% to < 20%; high ≥ 20%). This retrospective study comprised 20,772 participants in an employer-sponsored health assessment. High MPO associated with impaired kidney function with low (OR 2.2, 95% CI 1.6–3.7) and intermediate (OR 2.0, 95% CI 1.3–3.5) ASCVD risk, and with high FIB-4 or NAFLD scores in low (OR 2.4, 95% CI 1.2–4.7), intermediate (OR 3.1, 95% CI 2.0–6.0), and high (OR 3.8, 95% CI 2.9–7.4) ASCVD risk groups. High MPO was associated with markers of CKD and liver fibrosis in low to intermediate ASCVD risk and treated groups. These findings demonstrate the commonality of cardiometabolic biomarkers across multiple organs.   Prospective studies are warranted to assess whether high MPO levels identify persons at risk for CKD and liver fibrosis who may benefit from preventive strategies.